Using Product Package to Improve the Student's Writing Ability in Procedure Text at Seventh Grade of SMP Sunan Bonang Kraton - Rusmawan, Putu; Rahmania, Desy (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2017)
The objective of this research was to improve the students’ writing skill in procedure text by using product package for the seventh grade students on second semester 0f 2016-2017 academic years at SMP Sunan Bonang Kraton. This research used collaborative classroom action research design. This research was conducted in two cycles. The result of the post test at the end of meeting in first cycle showed that there were 40% students got ≤70. The second cycle, there were 18 students got score ≥ 70 with the highest score is 95 and lowest score is 66 and students’ success reached 90%.